If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(y+5)-8y=13
We move all terms to the left:
5(y+5)-8y-(13)=0
We add all the numbers together, and all the variables
-8y+5(y+5)-13=0
We multiply parentheses
-8y+5y+25-13=0
We add all the numbers together, and all the variables
-3y+12=0
We move all terms containing y to the left, all other terms to the right
-3y=-12
y=-12/-3
y=+4
| f(4)=3-^4 | | -8(1-5p)=-8-8p | | f(4)=3-2 | | 10+2x-14=x+4 | | g(529)=6(529^2)+36(529)−17 | | 3(4x2+8x-5)=4x(3x+2) | | 26=-(4-2j) | | -4x-3=3x-4 | | x-4/5=-7/15 | | 73y=72y-4 | | (8x+2)=2x+16 | | -2x+12=-2x—12 | | 2(-5x+3)=-34 | | (3x-15°)=(5x-23°) | | 8x-14-5x+48=0 | | 5(8-5x)=165 | | (x-3)/5=-8 | | -32-8m=-8m+-32 | | 9x-19/18-8x=4/18+4/18 | | 5r-18=-42+r | | 1.08(2t+2.50)+3=13.08 | | 4/7-0.8w+6=-1.2 | | 5x6+8x-12=0 | | 8x-14+11+63x=0 | | 2z+5(6z-3)=241 | | 6+7x=5.2x+12.3 | | -30-3y=-5(6+6y) | | 0.12+0.10(15000-x)=1600 | | -55=8+7(x-5) | | 45-3x=6x+23 | | 6x2+3x-5=2(3x2+x+2) | | -5(-4+2w)=-50 |